2020
DOI: 10.1101/2020.05.12.090464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-limited alterations in cortical activity of a Knock-in mice model ofKCNQ2-related Developmental and Epileptic Encephalopathy

Abstract: De novo variants in the KCNQ2 gene encoding the Kv7.2 subunit of the voltage-gated potassium Kv7/M channel are the main cause of Early Onset Epileptic Encephalopathy (EOEE) with suppression burst suggesting that this channel plays an important role for proper brain development. Functional analysis of these variants in heterologous cells has shown that most of them are loss of function leading to a reduction of M current. However the cellular mechanism of the neuronal network dysfunctionning is still not known.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 96 publications
(155 reference statements)
1
3
0
Order By: Relevance
“…In good agreement with the results obtained studying seizures, heterozygous p.(G279S) and p.(T274M) DEE mouse models showed a significant decrease of I M and an increase of neuronal excitability in hippocampal and cortical cells, respectively, 37 , 40 whereas SeLFNE p.(A306T) and p.(Y284C) models showed a decrease in I M only when the variants were homozygous. 34 , 35 DEE variants cause the most important loss of M current with less than 50% of current density, whereas SeLFNE variants lead to an M‐current density of 50% to 100%, 60 supporting a proportional relationship between the severity of epileptic behavior and the decrease in I M .…”
Section: Study Of the M Currentsupporting
confidence: 89%
See 2 more Smart Citations
“…In good agreement with the results obtained studying seizures, heterozygous p.(G279S) and p.(T274M) DEE mouse models showed a significant decrease of I M and an increase of neuronal excitability in hippocampal and cortical cells, respectively, 37 , 40 whereas SeLFNE p.(A306T) and p.(Y284C) models showed a decrease in I M only when the variants were homozygous. 34 , 35 DEE variants cause the most important loss of M current with less than 50% of current density, whereas SeLFNE variants lead to an M‐current density of 50% to 100%, 60 supporting a proportional relationship between the severity of epileptic behavior and the decrease in I M .…”
Section: Study Of the M Currentsupporting
confidence: 89%
“…As observed in the conditional KO (cKO) model, the p.(I205V) model displayed an increased excitability in L2/3 pyramidal cells 24,25 . For the other models, a severe phenotype was observed with spontaneous epileptic seizures ranging from partial seizures to generalized tonic‐clonic, accompanied by cognitive deficits consisting of learning and memory deficits, hyperactivity, and a decrease in the M current 37‐40 . To explore the consequences of M‐current suppression for the epileptic phenotype, a homozygous model was created bearing the variant p.(S559A), which attenuates the neurotransmitter‐induced M‐current suppression 41 .…”
Section: Knock‐in Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during chronically induced hyperexcitability, neurons downscale their intrinsic excitability and alter the size and location of the AIS ( Turrigiano and Nelson, 2004 ; Grubb and Burrone, 2010 ; Wolfart and Laker, 2015 ). Interestingly, Biba et al, recently reported that pyramidal neurons in heterozygous knock-in mice harboring the loss-of-function pathogenic T274M variant, exhibited hyperexcitability early on (P7-P9), but this effect went away in later life (P28-35; Biba et al, 2020 ). While the involvement of other channels, or the AHP specifically, were not examined, these results suggest that homeostatic changes also take place in neurons in vivo as a consequence of mutant KCNQ2 .…”
Section: Discussionmentioning
confidence: 99%